1973
DOI: 10.11606/issn.2526-3366.bzbm.1973.121317
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mysidacea (Crustacea) in the Cananeia region

Abstract: Este trabalho apresenta o estudo de alguns aspectos ecológicos das espécies hipopelágicas de Mysidacea, coletadas na região lagunar de Cananéia, entre Lat. 25º04'S-24º58'S e Long. 47º54'W-47º56'W.Na realização deste trabalho foram utilizadas amostras de plâncton, coletadas mensalmente em 12 estações, localizadas desde a proximidade da Barra de Cananéia até o interior dos "marigots". Coletas de plâncton foram feitas em profundidade, com rede D e, em superfície, com rede cônica de zooplâncton.É analisada a distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Although mysids were present throughout the year, their presence in Spring was conspicuous and consequently, the prey item most readly available and consumed by the fishes of groups I and II. Metamysidopsis elongata at/antica, the most numerous speaes in the dredging and in flSh stomach contents in Cananéia, coinci.dently revealed its maximum in Spring, according to Almeida Prado (1973). Furthermore, the present data showed that crustaceans are the most abundant group of the fauna.…”
Section: Discussionsupporting
confidence: 66%
“…Although mysids were present throughout the year, their presence in Spring was conspicuous and consequently, the prey item most readly available and consumed by the fishes of groups I and II. Metamysidopsis elongata at/antica, the most numerous speaes in the dredging and in flSh stomach contents in Cananéia, coinci.dently revealed its maximum in Spring, according to Almeida Prado (1973). Furthermore, the present data showed that crustaceans are the most abundant group of the fauna.…”
Section: Discussionsupporting
confidence: 66%
“…Seasonal migrations of shallow water mysids have been reported from Europe (Tattersall, 1938;Vorstman, 1951;Holthuis, 1954;Kinne, 1955;Mauchline, 1967;and Hesthagen, 1973), South America (Almeida Prado, 1973), Australia (Hodge, 1963), and Russia (Zmudzinski, 1967). Migrations of N. americana have not been reported, but seasonal changes in distribution have been suggested by Black (1956), Hulburt (1957), andHerman (1963).…”
Section: Allenmentioning
confidence: 99%
“…Esses crustáceos foram mencionados como ocorrentes em águas litorâneas brasileiras somente no Rio de Janeiro ẽ m São Paulo (COSTA, 1964;BACESCU, 1968a, b, c, 1969, SILVA, 1970a, b, 1971aALMEIDA PRADO, 1973, 1974REIS & SILVA, 1987). SILVA (197Ib) (Zimmer) C I. Telso com 18-32 lâminas distais situadas entre 2 dentes laterais; ápice com 3 lâmi-nas não articuladas: a lâmina mediaI mais curta e as duas laterais longas (Figs.…”
Section: Introductionunclassified